(untitled) (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2026)
The tourism sector in the Special Region of Yogyakarta (DIY) is dominated by an increasing number of informal workers, whose legal status remains ambiguous and is not explicitly regulated by national labor law. This situation creates a legal vacuum, as Law No. 13 of 2003 only recognizes formal employment relationships, thus neglecting the guarantee of protection and fulfillment of the rights of informal tourism workers. This research aims to formulate an ideal concept for fulfilling the rights of tourism sector workers based on local wisdom that is adaptive to the law. Employing a juridical-empirical research method, the study finds that the practice of fulfilling workers’ rights in DIY heavily relies on informal work patterns without written contracts, which creates flexibility but simultaneously causes job and income uncertainty. Amidst the weak intervention of formal regulation, local wisdom values such as gotong royong (mutual cooperation), tepo sliro (empathy/tolerance), and ngajeni (mutual respect) function as a "social umbrella" that maintains solidarity and harmony. As a solution, this research proposes a hybrid model that integrates formal protection with local cultural values. This concept includes four main elements: legal recognition of informal workers, implementation of a flexible social security scheme, establishment of minimum protection standards for wages and occupational safety, and empowerment of local communities as government partners. This model is expected to ensure the welfare of workers justly and sustainably without eliminating the cultural character that defines Yogyakarta’s tourism identity.